THE USE OF L1 IN L2 CLASSROO MANDITS IMPACT ON LEARNING PROCESS - :Khalida ALLAL.Iman OMRANI, Dr.MohammedDjemouiSaber (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
ABSTRACT This exploratory sequential mixed methods study (Creswell, 2015) signifies the role offirst language (L1) in second language (L2) instruction. The study, was carried out at four publicschools in Algeria (M’sila) where Arabic is the L1 of both teachers and students, and Englishis taught as a foreign language, explored Algerian English as a Foreign Language (EFL)teachers’ (N=7) attitudes toward using Arabic (L1) to teach English (L2) and the perceivedfunctions and/or negative ramifications of such use. It additionally investigated 104 first yearLiterary Stream students’beliefsregardingtheirteachers’useofL1intheL2classroom.Twosets of interviews (preobservation and post-observation), questionnaires, and seven class-observations were used to collect data. According to the findings, EFL teachers were highlyawareoftheneedoflimitingL1use,whichwasimpactedbythekindofcoursesandstudents'profi ciencylevels.ThestudysuggeststhatteachersemployedL1toperformsixdifferentrolesin the L2 classroom that they thought would improve L2 teaching and learning, (i.e., translation,metalinguistic use,overcomingcertaindifficultiesintheclassroom,givinginstructions,motivation, and avoiding some terms in L2 that are considered prohibited in L1), they alsoconsidered that excessive L1 usage may hinder L2 growth and it may also have negativeaffective ramifications. Thestudents'perceptions oftheirteachers' motivationsforutilizing theL1 in the classroom mirrored the teachers'. The findings ofthis study offer a clear image of L2teaching in foreign environments, implying that policymakers should reconsider L2 teachinglawsthatcurrentlydonotallowanyroleforL1intheL2classroom.
Keywords: Keywords:FirstLanguage,SecondLanguage,EFLclassroom,AlgerianSecondarySchool.